(untitled) (Educational Knowledge, 2017)
The knowledge or information society is constantly evolving, affecting most of the world’s population in all aspects of daily life. This has led to the emergence of increasingly sophisticated technological devices, which quickly become obsolete due to the emergence of others that are more attractive in terms of design or innovative applications. One of the fundamental aspects of the knowledge society is having access to a vast amount of information available through various media, with the possibility of sharing it with an unlimited number of people via virtual networks, which can generate significant advantages. Therefore, the objective of this work was to analyze the elements that facilitate and hinder information accessibility, not only for people with disabilities or special educational needs, but for all users who need to access information contained in a document, presentation, or website; aspects that are not always known, considered, or valued by those who bear the great responsibility of transmitting information.